A Qualitative Investigation into Financial Strategy, Performance, Investment Decision-Making - Daming, Sudirman; Widyawati, Widyawati (Economics and Digital Business Review, 2025)
This study aims to explore key aspects of financial management, including financial strategy, performance evaluation, and investment decision-making, through a qualitative investigation and comprehensive literature review. The research method involved synthesizing existing literature from diverse sources to identify trends, challenges, and opportunities in financial management practices. The findings highlight the multifaceted nature of financial strategy formulation, emphasizing the importance of aligning strategies with organizational objectives and integrating sustainability principles. Moreover, the study underscores the significance of performance evaluation in assessing organizational effectiveness, with frameworks like the Balanced Scorecard providing valuable tools for comprehensive performance assessment. In investment decision-making, the research emphasizes the need for robust processes incorporating quantitative analysis, qualitative assessments, and risk management techniques to optimize returns and mitigate risks effectively. Key findings include the importance of capital budgeting, project evaluation, and portfolio management in investment decisions and the growing influence of technological advancements on decision-making processes. Overall, this study contributes to a deeper understanding of financial management practices and highlights avenues for future research in sustainability integration and technological implications.